Analisis Daya Piezoelektrik Pada Alat Pencegahan Penyebaran Coronavirus Terintegrasi IoT - Lutfi Zulva Hanifah; Beni Putra Kurniawan; Yulfi Arista; Lucky Putri Rahayu (Politeknik Negeri Batam, 2022)
The innovation of the health protocol system for the prevention of the corona virus with an energy source of piezoelectric as independent electricity, namely the use of the concept of energy harvesting, converts the vibration or pressure generated by the footrests into electrical energy. The prototype system uses a piezoelectric ladder to generate power and a charging module to recharge from the battery. The power required is 60 watts. The charging aims to activate the entire system, namely by washing hands and sensors detecting masks and measuring body temperature which are all carried out in parallel. The camera sensor is able to distinguish the use of masks, so that your photos will be accurate and consistent. The Raspberry Pi controller communicates with the website server, which in turn controls various aspects of the system. The results of the process will be integrated with IoT and stored in a database, and the results will be displayed on a website as a monitoring process. If the system determines that the required health protocols are complete, the door will open automatically. The camera sensor accuracy is averaged out to be 98.5% accurate. In testing the whole system with around 40 kg of mass, which results in an average output voltage of 3.18 V and a current of 1.38 A and a foot step 3.517, 50 kg, the output voltage was 3.88 V, Current was 2.08 A and a step of 2,298 feet and 60 kg, resulting in an average voltage of 5.28 V, a current of 3.42 A and an average pedestrian frequency of 1.494.